Susanne Bier's nomadic perspective on home. Issue 3 (1st September 2018) - Molloy, Missy
Film critics and scholars have frequently linked concepts of cinematic transnationalism to Susanne Bier's films, which feature many characters in limbo, uncertain about which nation, culture and/or place they belong. This article proposes a nomadic dimension to the treatments of home, identity and intimacy in many films directed by Bier. Sensitivity to characters who have difficulty establishing permanent living spaces is particularly apparent in Bier films that utilize homes under renovation to model changes in characters' circumstances, priorities and desires. Closely reading the erotics of design in Den eneste ene (The One and Only) (Bier, 1999) and Elsker dig for evigt (Open Hearts) (Bier, 2003) indicates an authorial predilection for homes under renovation never seen through to completion.